ANALISIS EFISIENSI PEMASARAN BAGLOG DAN JAMUR TIRAM PUTIH PADA UD AROMA JAMUR DI KABUPATEN LUMAJANG - Dadang Adi Kusuma; Evita Sholiha Hani; Julian Adam Rijal (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2018)
Demand for white oyster mushroom continues to increase because it has a good nutritional content. The increasing mushroom demand positively affects the needs of baglog and white oyster mushroom, causing many producers who work baglog and white oyster mushroom one of them is UD Aroma Jamur. Research conducted at UD Aroma Jamur aims to know: (1) marketing channel of baglog and white oyster mushroom; (2) marketing function of each marketing agency of baglog and white oyster mushroom; (3) the efficiency and marketing margin of baglog and white oyster mushroom. Location of research in UD Aroma Jamur is determined intentionally (Purposive Method). Sampling used is purposive sampling and snowball sampling. The data used are primary and secondary data analyzed by using margin analysis and marketing efficiency. The results of the study showed that: (1) The marketing channel of baglog consist of zero-level channel, one-level, two-level. The white oyster mushroom marketing channel consists of a zero-level, a two-level, three-level, and four-level: (2) marketing functions undertaken by marketing agencies of baglog and white oyster mushroom, is a function of purchasing, sales function, transport function, storage function, market information function, risk function, packaging function, and sorting function: (3) an efficient marketing channel of baglog is a one level channel with marketing margin of Rp. 1,000 / baglog and profit share equal to 87,5% and efficiency value equal to 12,5%. The most efficient white oyster mushroom marketing channel is a two-tier channel with a marketing margin of Rp. 5.250 / kg and a profit share of 94.77% and an efficiency rating of 4.54%.